Impact of the Chilean educational reform on the teaching practice of physical education teachers (Praxis Educativa, 2012)
The Chilean Educational Reform proposes changes in the teaching and learning practices that call for research regarding educational practices as a way to know and understand what we are currently doing, and also regarding the ways in which we can improve our teaching practice. In this study, some teachers from the province of Ñuble were interviewed on some specific aspects of their educational tasks, and about their views in relation to their own way of teaching Physical Education at schools.
Keywords: educational reform; physical education teachers; changes in the teaching practices